Lignin-based carbon-coated nano-graphite composite negative electrode material and preparation method and application thereof

CN122907576APending Publication Date: 2026-10-13GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611285589.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但是,由于硬碳内部存在大量封闭孔结构和缺陷结构,在首次嵌锂过程中,消耗大量Li+,生成过多的SEI膜,带来较高的不可逆容量

Benefits of technology

[0034](1)本发明选用的材料来源广泛、成本低廉,木质素含有大量的含氧官能团,可以提供充足的活性位点,作为制备硬碳包覆层的碳源,通过包覆改性,在纳米石墨表面构筑硬碳保护屏障,经过高温烧制后,制备出包覆均匀的复合材料,有效提升了木质素包覆复合负极材料的电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907576A_ABST
    Figure CN122907576A_ABST
Patent Text Reader

Abstract

The application discloses a lignin-based carbon-coated nano-graphite composite negative electrode material and a preparation method and application thereof, and specifically comprises the following steps: (1) mixing nano-graphite, hard carbon, lignin, a phenolic compound, an ethanol aqueous solution and ammonia water, heating and stirring until completely dissolved, then adding a formaldehyde solution, drying and solidifying to obtain a precursor; (2) performing high-temperature carbonization treatment on the precursor under an inert gas atmosphere to obtain a composite negative electrode material. The application utilizes the rich oxygen-containing functional groups in lignin and phenolic aldehyde resin to tightly combine with defect sites on the surfaces of nano-graphite and hard carbon, the lignin phenolic aldehyde resin is uniformly coated on the surfaces of nano-graphite and hard carbon particles, an integrated carbon coating layer is formed through resin polymerization and high-temperature solidification, the structure of the nano-graphite and hard carbon in the composite particles is regulated, the ion transmission channel and interface stability of the composite negative electrode are optimized, and the capacity, rate performance and long cycle performance of the composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lignin-carbon anode materials, specifically relating to a lignin-based carbon-coated nanocomposite anode material, its preparation method, and its application. Background Technology

[0002] While the electric vehicle industry is booming, the market penetration rate of battery-powered vehicles remains relatively low compared to traditional vehicles. This is mainly due to range anxiety caused by the lower energy density of lithium-ion batteries and the slow charging speed of lithium-ion batteries. Most mainstream electric vehicles on the market cannot fully charge their batteries to 80% in 20 minutes. Therefore, developing lithium-ion batteries (LIBs) with fast charging capabilities and long cycle life is of great significance. The operation of LIBs is fundamentally based on Li... + Intercalation and deintercalation in positive and negative electrode materials. Commercially available lithium-ion batteries commonly use layered oxides and lithium iron phosphate as positive electrodes, and graphite as the negative electrode material. Graphite has a theoretical lithium storage capacity of only 372 mAh / g, but its rate performance is low and its charging speed is slow. Therefore, improving the charging speed of graphite plays a crucial role in the fast-charging capability of lithium-ion batteries.

[0003] Graphite has a layered stacked structure, formed by the stacking of graphene layers through van der Waals forces. Lithium intercalation in graphite is a multi-step process; the potential gradually decreases as the number of intercalated lithium ions increases. During LIB charging, lithium ions intercalate into the graphite anode. The lithium ion intercalation process includes the following steps: Li... + Diffusion from electrolyte, Li + Passing through the negative electrode-electrolyte interface, Li + Diffusion within graphite causes the graphite lattice to rearrange. The desolvation process of lithium ions on the electrode surface has a high energy barrier, which is one of the factors limiting the charging of graphite anodes.

[0004] Graphite anodes, due to their long-range crystal structure, have a longer lithium-ion diffusion path, resulting in slower lithium-ion diffusion. Nanographite, compared to ordinary graphite, has a smaller particle size, which can shorten the lithium-ion diffusion path. +The solid-phase diffusion distance within graphene sheets reduces electrode polarization and charge transfer resistance, effectively improving the rate performance of the material. However, the large specific surface area of ​​nanographite increases the contact area between the electrode and the electrolyte. During the initial charge-discharge cycle, this induces significant electrolyte decomposition, generating excessive SEI film, increasing irreversible capacity, and causing a decrease in initial coulombic efficiency. Secondly, nanographite exposes numerous active sites on its edges and end faces. These sites have high electrochemical activity, not only continuously triggering interfacial side reactions but also easily causing solvent molecules and lithium ions to co-intercalate into the graphite layers, damaging the graphite sheet structure and leading to sheet peeling under long-term cycling, resulting in continuous capacity decay. Therefore, a coating layer can be introduced to modify nanographite. The coating layer can physically cover numerous active edge and end face sites on nanographite, blocking direct contact between the electrolyte and the active graphite surface, inhibiting excessive electrolyte decomposition, reducing disordered SEI film growth, and improving initial coulombic efficiency.

[0005] Hard carbon possesses a disordered, interwoven carbon framework, larger interlayer spacing, and abundant porous structure, exhibiting strong tunability of its microstructure. As a coating layer, it can be used for Li... + Providing ample lithium storage sites and a larger interlayer spacing is beneficial for Li + The insertion and extraction of lithium. However, due to the large number of closed pores and defects inside hard carbon, a large amount of Li is consumed during the initial lithium insertion process. + Excessive SEI film formation leads to high irreversible capacity. Summary of the Invention

[0006] The primary objective of this invention is to provide a method for preparing a high-rate-performance lignin-based carbon-coated composite anode material. Specifically, it involves coating nano-graphite and hard carbon with lignin phenolic resin to regulate the structure of the two materials within the composite material, thereby improving the charging rate performance of the anode.

[0007] Another objective of this invention is to provide a high-rate, low-cost lignin-based carbon-coated composite anode material prepared by the above-described method.

[0008] Another object of the present invention is to provide the above-mentioned high-rate lignin-based composite anode material as an anode material for lithium-ion batteries.

[0009] The objective of this invention is achieved through the following technical solution:

[0010] A method for preparing a lignin-based carbon-coated composite anode material includes the following steps:

[0011] (1) Mix nano-graphite, hard carbon, lignin, phenolic compounds, ethanol aqueous solution and ammonia water, heat and stir the resulting mixture until completely dissolved, add formaldehyde solution and heat to react, and dry to obtain lignin phenolic resin coated nano-graphite composite material precursor.

[0012] (2) The precursor is carbonized in an inert gas atmosphere to obtain the coating material.

[0013] Preferably, the mass ratio of nanographite to lignin is 20:1 to 2:1, the mass ratio of hard carbon to nanographite is 10:1 to 1:10, and the mass ratio of lignin to phenol is 3:1 to 1:3.

[0014] Preferably, the mass ratio of nanographite to lignin is 10:1 to 5:1, the mass ratio of hard carbon to nanographite is 2:1 to 1:3 (most preferably 1:1), and the mass ratio of lignin to phenol is 1 ± 0.5:1.

[0015] Preferably, the mass concentration of ethanol in the mixture in step (1) is 20%-40%, and the mass concentration of ammonia is 1%-10%.

[0016] Preferably, the volume ratio of ethanol to water in the ethanol-water solution is 1 ± 0.5:1; and the mass concentration of the ammonia solution is 2%-5%.

[0017] Preferably, the mass ratio of formaldehyde to lignin is 1 ± 0.5:10; and the mass concentration of the formaldehyde solution is 1%-5%.

[0018] Preferably, the heating reaction in step (1) is carried out at a temperature of 50°C to 100°C for 1 hour to 24 hours; the carbonization in step (2) is carried out at a temperature of 800°C to 1500°C for 1 hour to 4 hours.

[0019] Preferably, the heating reaction in step (1) is carried out at a temperature of 60±5℃ for 3±1h, and then the temperature is raised to 90±5℃ for 3±1h; the carbonization in step (2) is carried out at a temperature of 1000~1200℃ for 2±0.5h.

[0020] Preferably, the heating rate of carbonization in step (2) is 1 to 30 °C / min, and the flow rate of the inert gas is 2 to 100 mL / min; more preferably, the heating rate of carbonization is 5 °C / min, and the flow rate of the inert gas is 50 mL / min.

[0021] Preferably, the inert gas in step (2) is at least one of nitrogen, argon and helium.

[0022] Preferably, the lignin in step (1) is at least one of alkali lignin, enzymatically hydrolyzed lignin, and lignin sulfonate; more preferably, the enzymatically hydrolyzed lignin is the residue of enzymatically hydrolyzed lignin obtained from the bio-smelting process; the alkali lignin is alkali lignin extracted from papermaking black liquor; and the lignin sulfonate is lignin sulfonate extracted from sulfite pulping liquor.

[0023] Preferably, the phenolic compound in step (1) is at least one of phenol, cresol, and xylenol. Preferably, the drying temperature in step (1) is 60–80°C and the drying time is 12–36 h.

[0024] Application of the lignin-based carbon-coated composite anode material prepared by the method in lithium-ion batteries.

[0025] The high-rate lignin-based carbon-coated composite anode material of this invention is used to fabricate lithium-ion battery anodes:

[0026] Weigh out the lignin-based carbon-coated composite negative electrode material (active material), conductive carbon black conductive agent, and sodium alginate (SA) binder in a mass ratio of 8:1:1. Dissolve the SA in an appropriate amount of water and stir until completely dissolved. Then mix the uniformly ground active material and conductive carbon black with the SA in proportion and grind until uniform. Then coat the slurry onto a round copper foil (12 mm in diameter) and dry it in a vacuum oven at 80 ℃.

[0027] The prepared electrode sheets, lithium sheets, and separator were assembled into a CR2025 button-type lithium-ion battery in a glove box filled with high-purity argon gas. The electrolyte was a 1 mol / L LiPF6 lithium-ion secondary electrolyte. The charge-discharge performance and cycle stability of the lithium-ion battery were tested using a battery testing system.

[0028] This invention enables the construction of high closed-pore volume in lignin-based carbon-coated composite anode materials, providing abundant filling sites for lithium ions within the closed pores of hard carbon, thereby achieving high plateau capacity. Specifically, it includes the following aspects:

[0029] This invention leverages the difference between the regular layered structures of hard carbon and graphite to overcome the limitations of single-material performance. Nano-graphite dispersed within the hard carbon matrix constructs a continuous electronically conductive network, effectively reducing the overall electrode impedance and improving rate performance. The disordered carbon framework of hard carbon buffers the localized micro-deformations generated during the lithium insertion and extraction processes of graphite, enhancing the stability of the material structure. Simultaneously, due to the high lithium insertion potential of hard carbon, it provides abundant lithium ions for the insertion of lithium ions into the nano-graphite, thereby reducing the insertion overpotential. This invention employs a composite coating strategy. The outer coating layer passivates surface defects in hard carbon and active edges of the nano-graphite, reducing the specific surface area of ​​the composite material, inhibiting excessive electrolyte decomposition, mitigating disordered SEI film growth, and improving the first coulombic efficiency. The coating shell disperses nano-graphite and hard carbon within the carbon material framework, ensuring a tight bond between them. Simultaneously, the coating layer provides stress buffering, suppressing the generation of micro-cracks during lithium insertion and extraction, and maintaining the integrity of the carbon electrode structure. After coating modification, the composite material achieves synergistic optimization of reversible capacity, rate performance and long cycle performance.

[0030] This invention utilizes the abundant phenolic hydroxyl groups of lignin to partially replace phenol in the reaction with formaldehyde. Under alkaline conditions, the hydroxyl groups of lignin undergo etherification with hydroxymethyl groups, forming ether bonds and cross-linking to create a three-dimensional phenolic network structure. Phenol is a small aromatic phenol molecule, and lignin is a high aromatic phenol polymer; their polarities and surface energies are similar, resulting in almost no obvious interfacial defects when blended under molten or liquid-phase conditions. The π-π stacking between benzene rings further enhances the system's compatibility. Further coating with nano-graphite and hard carbon, followed by high-temperature carbonization, gives the prepared lignin-coated material excellent rate performance.

[0031] In this invention, the catalyst plays a partial role in the structure of resin molecules, coating uniformity, and electrochemical performance. The synthesis of lignin-phenolic resin can utilize various alkaline catalysts, such as inorganic bases and organic amines. When strong inorganic bases are used as catalysts, they easily introduce metal ions into the sample, which remain in the carbon coating layer after carbonization, negatively impacting the electrochemical performance of the composite negative electrode. High-boiling-point organic amines tend to leave nitrogen residues. Ammonia, as a weakly volatile organic base, can be volatilized and removed during the high-temperature carbonization stage, leaving no metal impurities. Its mild alkalinity allows for the regulation of the resin condensation rate, facilitating the formation of a uniform and complete resin coating layer on the nano-graphite surface. Furthermore, the resulting resin exhibits a high carbonization rate. Therefore, ammonia was chosen as the catalyst for the condensation reaction in this experiment. Phenolic resin is a polymer synthesized from phenols (such as phenol, formaldehyde, and xylenol) and aldehydes (such as formaldehyde, acetaldehyde, and furan) at a certain temperature through acid or base catalysis. Lignin can undergo phenolation with phenol, replacing the benzene ring in phenol to form phenolic resin.

[0032] In summary, this invention selects lignin-phenolic resin, rich in oxygen-containing functional groups and possessing a three-dimensional network structure, as the carbon source and coating precursor. This resin is uniformly coated onto the surface of nano-graphite particles, and then in-situ polymerization and thermosetting are used to form a continuous and stable coating layer on the nano-graphite surface. During high-temperature carbonization, the lignin-phenolic resin gradually transforms into a carbon layer, which is firmly loaded onto the surface of the nano-graphite composite material. This alleviates the recombination of graphite sheets and improves the interfacial compatibility and structural stability of the composite material. Subsequently, in a nitrogen atmosphere above 800°C, the coating layer is further carbonized to form a porous network structure, thus preparing the lignin-phenolic resin composite material. This method not only uses environmentally friendly and inexpensive lignin-phenolic resin as the main precursor but also modifies the graphite surface through a simple coating carbonization method, eliminating the need for additional strong acid or alkali treatments. The lignin-phenolic resin-coated nano-graphite composite material prepared by this method exhibits excellent pore structure, high specific surface area, and good electrochemical performance.

[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0034] (1) The materials selected in this invention are widely available and inexpensive. Lignin contains a large number of oxygen-containing functional groups, which can provide sufficient active sites as a carbon source for preparing hard carbon coating. Through coating modification, a hard carbon protective barrier is constructed on the surface of nano-graphite. After high-temperature firing, a uniformly coated composite material is prepared, which effectively improves the electrochemical performance of lignin-coated composite negative electrode material.

[0035] (2) The present invention uses a method of coating nano-graphite and hard carbon with lignin phenolic resin to prepare precursors. The rich oxygen-containing functional groups in lignin and phenolic resin are tightly bound to the active sites on the surface of nano-graphite. The lignin phenolic resin is uniformly coated on the surface of graphite particles. A continuous and complete carbon coating layer is formed by resin polymerization and high temperature curing. The pore structure inside the hard carbon layer is regulated, and the ion transport channels and interface stability of the composite negative electrode are optimized.

[0036] (3) The present invention utilizes a continuous coating network formed by cross-linking of lignin phenolic resin, which effectively inhibits the high-temperature sintering and agglomeration of nano-graphite particles, ensuring that the coating layer uniformly and completely encapsulates the nano-graphite and hard carbon matrix, avoiding the blockage of ion transport channels caused by direct contact and stacking of nano-graphite particles, thereby preventing the problem of large-area cracking and peeling of the hard carbon coating layer caused by the expansion of graphite volume during battery discharge.

[0037] (4) This invention uses lignin-phenolic resin as a coating precursor. The resin carbonization layer achieves a dual-layer modification and regulation effect on the nano-graphite matrix and hard carbon. Specifically, during the heating process, the lignin-phenolic resin undergoes pyrolysis and solidification at 300-500℃, forming a continuous and uniform pre-coated carbon layer on the surface of the nano-graphite, isolating the direct contact between the nano-graphite particles. Above 800℃, the resin is fully carbonized and accompanied by the pyrolysis of a small amount of oxygen-containing functional groups, which in-situ activates the surface hard carbon layer and graphite layer. The dual-layer modification and regulation form a coating layer with both a dense framework and micro-mesopores, which is beneficial for buffering the volume expansion of lithium intercalation and deintercalation in the composite material and shortening the ion transport path.

[0038] (5) The lignin-phenolic resin-coated nano-graphite composite anode material prepared by this invention not only alleviates the problem of high-temperature agglomeration of nano-graphite particles, but also has the advantage of a thin and uniform hard carbon layer. The hard carbon coating layer formed by the high-temperature carbonization of lignin-phenolic resin not only constructs a stable conductive network for the nano-graphite matrix, but also buffers the volume expansion during the lithium insertion / extraction process of nano-graphite, providing a stable channel for the rapid transport of lithium ions in the nano-graphite composite anode material. Attached Figure Description

[0039] Figure 1 The image shows the carbon products of the lignin-phenolic resin-coated graphite composite anode material (ALPF@G-HC-1200) in Example 1 at 1200°C using SEM images.

[0040] Figure 2 This is a SEM image of the carbon products of the lignin-phenolic resin-coated nano-graphite composite anode material (ALPF@NG-HC-1200) in Example 2 at 1200°C.

[0041] Figure 3 The image shows the XRD pattern of the lignin-phenolic resin-coated graphite composite anode material (ALPF@G-HC-1200) from Example 1.

[0042] Figure 4 The image shows the XRD pattern of the lignin-phenolic resin-coated nano-graphite composite anode material (ALPF@NG-HC-1200) in Example 2.

[0043] Figure 5 The image shows the Raman diagram of the lignin-phenolic resin-coated graphite composite negative electrode material (ALPF@G-HC-1200) in Example 1.

[0044] Figure 6 Raman diagram of the lignin-phenolic resin-coated nano-graphite composite anode material (ALPF@NG-HC-1200) in Example 2.

[0045] Figure 7 Example 1: Lignin-phenolic resin-coated graphite composite anode material (ALPF@G-HC-1200); Example 2: Lignin-phenolic resin-coated nano-graphite composite anode material (ALPF@NG-HC-1200); Comparative Example 1: Lignin-phenolic resin (ALPF-1200); Comparative Example 2: Ordinary graphite (G); Comparative Example 3: Nano-graphite (NG) were used as anodes for lithium-ion batteries at 0.05 A•g. -1 The second charge-discharge curve at current density.

[0046] Figure 8 The graphs showing the specific capacitance as a function of current density are shown for the following examples: Example 1: lignin-phenolic resin-coated graphite composite anode material (ALPF@G-HC-1200); Example 2: lignin-phenolic resin-coated nano-graphite composite anode material (ALPF@NG-HC-1200); Comparative Example 1: lignin-phenolic resin (ALPF-1200); ordinary graphite (G); and nano-graphite (NG) used as anodes in lithium-ion batteries.

[0047] Figure 9Example 1: Lignin-phenolic resin-coated graphite composite anode material (ALPF@G-HC-1200); Example 2: Lignin-phenolic resin-coated nano-graphite composite anode material (ALPF@NG-HC-1200); Comparative Example 1: Lignin-phenolic resin (ALPF-1200), ordinary graphite (G), and nano-graphite (NG) were used as anodes for lithium-ion batteries at 0.1 A•g. -1 Cyclic curves at current density.

[0048] Figure 10 The image shows a SEM image of lignin-phenolic resin (ALPF-1200) from Comparative Example 1.

[0049] Figure 11 The image shows the XRD pattern of lignin phenolic resin (ALPF-1200) in Comparative Example 1.

[0050] Figure 12 The image shows the Raman diagram of lignin phenolic resin (ALPF-1200) for Comparative Example 1.

[0051] Figure 13 This is a SEM image of ordinary graphite (G).

[0052] Figure 14 The image shows the XRD pattern of ordinary graphite (G).

[0053] Figure 15 Raman plot of ordinary graphite (G).

[0054] Figure 16 This is a SEM image of nanographite (NG).

[0055] Figure 17 The image shows the XRD pattern of nanographite (NG).

[0056] Figure 18 Raman plot of nanographite (NG). Detailed Implementation

[0057] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the implementation of the present invention is not limited thereto.

[0058] Unless otherwise specified in the embodiments of this invention, the conditions shall be performed according to conventional conditions or conditions recommended by the manufacturer. All raw materials and reagents used, unless otherwise specified, are commercially available products.

[0059] Commercial hard carbon (Shandong Yongkun New Material Technology Co., Ltd., YKHC).

[0060] Nano-graphite (Nanjing Greenfa Carbon Materials Co., Ltd., 10,000 mesh graphite powder, 99% fixed carbon)

[0061] The lignin used in the examples was sodium lignin sulfonate, purchased from Zhejiang Jiefa Technology Co., Ltd.

[0062] Example 1

[0063] (1) Prepare 35 mL of ethanol-water solution with a volume ratio of 1:1. Add 5 g of graphite, 5 g of commercial hard carbon, 0.5 g of lignin, 0.5 g of phenol, and 2.5 mL of ammonia water as catalysts to the ethanol-water solution. Stir in an oil bath at 30 °C for 1 h until completely dissolved. Then add 2 mL of formaldehyde solution with a concentration of 1.25 mol / L. Stir in an oil bath at 60 °C for 3 h. Then raise the temperature to 90 °C and stir in an oil bath for 3 h.

[0064] (2) The liquid after the reaction in step (1) was heated and stirred at 90 °C for 8 hours for the first drying to obtain a wet composite material, named ALPF@G-HC.

[0065] (3) The ALPF@G-HC obtained in step (2) was placed in an 80℃ oven for a second drying for 24h to obtain the dried ALPF@G-HC precursor.

[0066] (4) The ALPF@G-HC precursor in step (3) was heated to 1200℃ for 2h under a nitrogen atmosphere and a gas flow rate of 50mL / min to obtain a lignin phenolic resin coated graphite composite anode material, named ALPF@G-HC-1200.

[0067] SEM and XRD results of ALPF@G-HC-1200 are as follows: Figure 1 and Figure 3 As shown. Figure 1 A thin film was observed to uniformly cover the surfaces of graphite and hard carbon, with the edges and corners of the particles also uniformly covered by phenolic resin. No large areas of exposed graphite or hard carbon were observed. Furthermore, the coating layer showed no obvious cracks, indicating a uniform and dense coating. The XRD pattern revealed sharp and complete graphite characteristic peaks, suggesting that the interior is ordered graphite, while the outer layer is an amorphous carbon layer carbonized with phenolic resin. Figure 5 This is the Raman spectrum of ALPF@G-HC-1200. The sample's I... D / I G The ratio is close to 1, indicating that the coated sample obtained after carbonization at 1200℃ is mainly composed of amorphous carbon. SEM, XRD, and Raman images all confirm that the phenolic resin successfully coated graphite and hard carbon.

[0068] Figure 7 ALPF@G-HC-1200 is used as the negative electrode in lithium-ion batteries at 0.05 A•g.-1 The second charge-discharge curve at the current density. At 0.05 A•g -1 At a current density of [value missing], ALPF@G-HC-1200 achieves a plateau capacity of up to 304 mAh•g in the second cycle. -1 The platform's capacity accounted for 72.9%.

[0069] Figure 8 The graph shows the specific capacitance of ALPF@G-HC-1200 used as the negative electrode in a lithium-ion battery as a function of current density. At 0.05 A•g... -1 At a current density of 405 mAh•g, ALPF@G-HC-1200 exhibits a current density of 405 mAh•g. -1 The specific capacity, at 2 A•g -1 At a current density of 100 mAh•g -1 The specific capacity indicates that ALPF@G-HC-1200 exhibits good rate performance when used as a negative electrode in lithium-ion batteries.

[0070] Figure 9 ALPF@G-HC-1200 is used as the negative electrode in lithium-ion batteries at 0.1 A•g -1 The graph shows the cycling performance at the specified current density. At this current density, ALPF@G-HC-1200 retains 98% of its capacity after 150 cycles. This indicates that ALPF@G-HC-1200 exhibits excellent cycle stability when used as a negative electrode in lithium-ion batteries.

[0071] Example 2

[0072] (1) Prepare 35 mL of ethanol-water solution with a volume ratio of 1:1. Add 5 g of nano-graphite, 5 g of commercial hard carbon, 0.5 g of lignin, 0.5 g of phenol, and 2.5 mL of ammonia water as catalysts to the ethanol-water solution. Stir in an oil bath at 30 °C for 1 h until completely dissolved. Then add 2 mL of formaldehyde solution with a concentration of 1.25 mol / L. Stir in an oil bath at 60 °C for 3 h. Then raise the temperature to 90 °C and stir in an oil bath for 3 h.

[0073] (2) The liquid in step (1) was heated and stirred at 90°C for 8 hours for the first drying to obtain a wet composite material, named ALPF@NG-HC.

[0074] (3) The ALPF@NG-HC obtained in step (2) was placed in an 80℃ oven for a second drying for 24h to obtain the dried ALPF@NG-HC precursor.

[0075] (4) The ALPF@NG-HC precursor in step (3) was heated to 1200℃ for 2h under a nitrogen atmosphere and a gas flow rate of 50mL / min to obtain a lignin phenolic resin coated nano-graphite composite anode material, named ALPF@NG-HC-1200.

[0076] Figure 2 , Figure 4 and Figure 6 The images show the SEM, XRD, and Raman spectra of ALPF@NG-HC-1200. The SEM images reveal that pure nanographite should exhibit a smooth, flat, sheet-like structure, while the surface of ALPF@NG-HC-1200 is rough, with wrinkled carbon layers at the edges, completely altering the original smooth morphology of the sheet. This indicates that phenolic resin is uniformly deposited on the surface of nanographite and hard carbon, forming a coating layer. The XRD pattern shows the presence of a characteristic peak of the graphite (002) crystal plane at 26.5°, indicating that the composite material possesses a complete ordered nanographite crystal structure. In the Raman spectrum, the intensity of the D peak is significantly increased, and the I peak... D / I G The increase also indicates that a large number of phenolic group defect carbon layers have been introduced into the graphite and hard carbon surfaces.

[0077] Figure 7 ALPF@NG-HC-1200 is used as the negative electrode in lithium-ion batteries at 0.05 A•g. -1 The second charge-discharge curve at the current density. At 0.05 A•g -1 At the current density, ALPF@NG-HC-1200 has a plateau capacity of up to 308 mAh・g⁻¹ in the second cycle, which accounts for 72.3% of the total reversible specific capacity.

[0078] Figure 8 The graph shows the specific capacitance of ALPF@NG-HC-1200 used as the negative electrode in a lithium-ion battery as a function of current density. At 0.05 A•g... -1 At a current density of 440 mAh•g, ALPF@NG-HC-1200 exhibits a current density of 440 mAh•g. -1 The specific capacity, at 2 A•g -1 At a current density of 200 mAh•g -1 The specific capacity indicates that ALPF@NG-HC-1200 exhibits good rate performance when used as a negative electrode in lithium-ion batteries.

[0079] Figure 9 ALPF@NG-HC-1200 is used as the negative electrode in lithium-ion batteries at 0.1 A•g -1The graph shows the cycling performance at the specified current density. At this current density, ALPF@NG-HC-1200 retains 99% of its capacity after 150 cycles, exhibiting high capacity. This demonstrates that ALPF@NG-HC-1200 possesses excellent cycle stability when used as a negative electrode in lithium-ion batteries.

[0080] Example 3

[0081] (1) Prepare 35 mL of ethanol-water solution with a volume ratio of 1:1. Add 5 g of nano-graphite, 5 g of commercial hard carbon, 0.5 g of lignin, 0.5 g of phenol, and 3 mL of triethylamine (TEA) as catalysts to the ethanol-water solution. Stir in an oil bath at 30 °C for 1 h until completely dissolved. Then add 2 mL of formaldehyde solution with a concentration of 1.25 mol / L. Stir in an oil bath at 60 °C for 3 h. Then raise the temperature to 90 °C and stir in an oil bath for 3 h.

[0082] (2) The liquid in step (1) was heated and stirred at 90°C for 8 hours for the first drying to obtain a wet composite material, named ALPF@NG-HC-TEA.

[0083] (3) The ALPF@NG-HC-TEA obtained in step (2) was placed in an 80℃ oven for a second drying for 24h to obtain the dried ALPF@NG-HC-TEA precursor.

[0084] (4) The ALPF@NG-HC-TEA precursor in step (3) was heated to 1200℃ for 2h under a nitrogen atmosphere and a gas flow rate of 50mL / min to obtain a lignin phenolic resin coated nano-graphite composite anode material, named ALPF@NG-HC-TEA-1200.

[0085] Example 4

[0086] (1) Prepare 35 mL of ethanol-water solution with a volume ratio of 1:1. Add 5 g of nano-graphite, 5 g of commercial hard carbon, 0.5 g of lignin, 0.5 g of phenol, and 4 mL of triethanolamine (TEOA) as catalysts to the ethanol-water solution. Stir in an oil bath at 30 °C for 1 h until completely dissolved. Then add 2 mL of formaldehyde solution with a concentration of 1.25 mol / L. Stir in an oil bath at 60 °C for 3 h. Then raise the temperature to 90 °C and stir in an oil bath for 3 h.

[0087] (2) The liquid in step (1) was heated and stirred at 90°C for 8 hours for the first drying to obtain a wet composite material, named ALPF@NG-HC-TEOA.

[0088] (3) The ALPF@NG-HC-TEOA obtained in step (2) was placed in an 80℃ oven for a second drying for 24h to obtain the dried ALPF@NG-HC-TEOA precursor.

[0089] (4) The ALPF@NG-HC-TEOA precursor in step (3) was heated to 1200℃ for 2h under a nitrogen atmosphere and a gas flow rate of 50mL / min to obtain a lignin phenolic resin coated nano-graphite composite anode material, named ALPF@NG-HC-TEOA-1200.

[0090] Example 5

[0091] (1) Prepare 35 mL of ethanol-water solution with a volume ratio of 1:1. Add 5 g of nano-graphite, 5 g of commercial hard carbon, 0.5 g of lignin, 0.5 g of phenol, and 1.2 mL of ethylenediamine (EDA) as catalysts to the ethanol-water solution. Stir in an oil bath at 30 °C for 1 h until completely dissolved. Then add 2 mL of formaldehyde solution with a concentration of 1.25 mol / L. Stir in an oil bath at 60 °C for 3 h. Then raise the temperature to 90 °C and stir in an oil bath for 3 h.

[0092] (2) The liquid in step (1) was heated and stirred at 90°C for 8 hours for the first drying to obtain a wet composite material, named ALPF@NG-HC-EDA.

[0093] (3) Place the ALPF@NG-HC-EDA obtained in step (2) in an 80℃ oven for a second drying for 24h to obtain the dried ALPF@NG-HC-EDA precursor.

[0094] (4) The ALPF@NG-HC-EDA precursor in step (3) was heated to 1200℃ for 2h under a nitrogen atmosphere and a gas flow rate of 50mL / min to obtain a lignin phenolic resin coated nano-graphite composite anode material, named ALPF@NG-HC-EDA-1200.

[0095] Comparative Example 1

[0096] (1) Prepare 35 mL of ethanol-water solution with a volume ratio of 1:1. Add 0.5 g of lignin, 0.5 g of phenol and 2.5 mL of ammonia as catalysts to the ethanol-water solution and stir in an oil bath at 30 °C for 1 h until completely dissolved. Then add 2 mL of formaldehyde solution with a concentration of 1.25 mol / L and stir in an oil bath at 60 °C for 3 h. Then raise the temperature to 90 °C and stir in an oil bath for 3 h.

[0097] (2) The liquid in step (1) is heated and stirred at 90°C for 8 hours for the first drying to obtain a wet material, named ALPF.

[0098] (3) The ALPF obtained in step (2) is placed in an 80℃ oven for a second drying for 24 hours to obtain the dried ALPF precursor.

[0099] (4) The ALPF precursor in step (3) is heated to 1200℃ for 2h under a nitrogen atmosphere and a gas flow rate of 50mL / min to obtain lignin phenolic resin anode material, named ALPF-1200.

[0100] Figure 10 , Figure 11 and Figure 12 The images show the SEM, XRD, and Raman spectra of ALPF-1200. The SEM image reveals a relatively smooth and flat surface. The XRD pattern shows a much larger interlayer spacing than natural graphite and hard carbon, indicating loose carbon layer stacking, small graphite crystallites, and short-range ordered carbon atoms with long-range disorder, suggesting this sample is typical amorphous carbon. The Raman spectra show clear characteristic peaks at the D and G points, indicating the presence of graphitic carbon and disordered defect carbon, further confirming that ALPF is amorphous carbon.

[0101] The lithium-ion battery electrode sheet prepared with ALPF-1200 was used as the working electrode, and the lithium metal sheet was used as the counter electrode. A lithium-ion half-cell was assembled using 1 mol / L LiPF6 as the electrolyte. The electrochemical performance of ALPF-1200 was tested. See details. Figure 7-9 .

[0102] Figure 7 ALPF-1200 is used as the negative electrode in lithium-ion batteries at 0.05 A•g. -1 The second charge-discharge curve at the current density. At 0.05 A•g -1 At a current density of [value missing], the plateau capacity of ALPF-1200 in the second cycle is only 230 mAh•g. -1 .

[0103] Figure 8 The graph shows the specific capacitance of ALPF-1200 used as the negative electrode in a lithium-ion battery as a function of current density. At 0.05 A•g... -1 At a current density of 370 mAh•g -1 The specific capacity, at 2 A•g -1 At a current density of 50 mAh•g -1 Specific capacity.

[0104] Figure 9 ALPF-1200 is used as the negative electrode in lithium-ion batteries at 0.1 A•g -1 The cycling performance diagram is shown at the specified current density. At this current density, ALPF-1200 exhibits 95% capacity retention after 150 cycles, but shows initial cycling instability.

[0105] Figure 13 , 14 Figures 1 and 15 show the SEM, XRD, and Raman images of ordinary graphite (G), respectively. The SEM image reveals that graphite exhibits a micron-scale sheet structure with smooth sheet surfaces. The XRD image shows a characteristic diffraction peak at (002) in G, indicating tightly and orderly stacked carbon layers and relatively large graphite crystallites. The Raman image shows that G is predominantly composed of ordered sp² graphitic carbon with few defects in the carbon framework structure.

[0106] The lithium-ion battery electrode sheet prepared by G was used as the working electrode, and the lithium metal sheet was used as the counter electrode. A lithium-ion half-cell was assembled using 1 mol / L LiPF6 as the electrolyte. The electrochemical performance of G was tested. See details. Figure 7-9 .

[0107] Figure 7 G in the figure is used as the negative electrode of a lithium-ion battery, at 0.05 A•g -1 The second charge-discharge curve at the current density. At 0.05 A•g -1 At a current density of [value missing], the plateau capacity of G in the second cycle is only 270 mAh•g. -1 .

[0108] Figure 8 The graph shows that G is used as the negative electrode in a lithium-ion battery, and its specific capacitance varies with current density. At 0.05 A•g -1 At a current density, G has 370 mAh•g -1 The specific capacity, at 2 A•g -1 At a current density of 50 mAh•g -1 Specific capacity.

[0109] Figure 9 G in the figure is used as the negative electrode of a lithium-ion battery, at 0.1 A•g -1 The cycling performance diagram is shown at the specified current density. At this current density, the capacity retention is 96% after 150 cycles, but the capacity is relatively low.

[0110] Figure 16 , Figure 17 and Figure 18The images show the SEM, XRD, and Raman spectra of nanographite (NG). The SEM image reveals that NG is composed of numerous nanosheets with small sheet sizes. The XRD image shows a sharp characteristic diffraction peak at (002), indicating that the carbon layers are tightly and orderly stacked with long-range ordered carbon atoms, suggesting that the sample retains the graphite crystal structure. The Raman spectra show clear characteristic peaks for D and G. Compared to ordinary graphite raw materials, the relative intensity of the D peak is increased, indicating that nanographite produces more edge structures and defects.

[0111] The lithium-ion battery electrode sheet prepared by NG was used as the working electrode, and the lithium metal sheet was used as the counter electrode. A lithium-ion half-cell was assembled using 1 mol / L LiPF6 as the electrolyte. The electrochemical performance of NG was tested. See details. Figure 7-9 .

[0112] Figure 7 NG in it is used as the negative electrode of lithium-ion batteries, at 0.05 A•g -1 The second charge-discharge curve at the current density. At 0.05 A•g -1 At a current density of 100 mAh / g, the plateau capacity of NG in the second cycle is only 300 mAh / g. -1 .

[0113] Figure 8 The graph shows the specific capacitance of NG used as the negative electrode in lithium-ion batteries as a function of current density. At 0.05 A•g -1 At a current density, NG has 390 mAh•g -1 The specific capacity, at 2 A•g -1 At a current density of 100 mAh•g -1 Specific capacity.

[0114] Figure 9 NG in it is used as the negative electrode of lithium-ion batteries, at 0.1 A•g -1 The cycling performance diagram is shown at the specified current density. At this current density, the capacity retention is 97% after 150 NG cycles, but the capacity is relatively low.

[0115] As can be seen from the comparison in the figure, the capacity, rate performance and cycle stability of the coated ALPF@G-800 and ALPF@NG-800 are significantly higher than those of ALPF, G and NG.

[0116] Table 1 shows the plateau capacity and specific capacity (test current density 50 mA•g) of the coated samples prepared by the above embodiments and comparative examples. -1 ), capacity retention rate after 150 long cycles.

[0117] Comparative Example 2

[0118] (1) Prepare 35 mL of ethanol-water solution with a volume ratio of 1:1. Add 5 g of graphite, 0.5 g of lignin, 0.5 g of phenol and 2.5 mL of ammonia as catalysts to the ethanol-water solution. Stir in an oil bath at 30 °C for 1 h until completely dissolved. Then add 2 mL of formaldehyde solution with a concentration of 1.25 mol / L. Stir in an oil bath at 60 °C for 3 h. Then raise the temperature to 90 °C and stir in an oil bath for 3 h.

[0119] (2) The liquid from step (1) was heated and stirred at 90°C for 8 hours for the first drying to obtain a wet coating material, named ALPF@G

[0120] (3) Place the ALPF@G obtained in step (2) in an 80℃ oven for a second drying for 24h to obtain the dried ALPF@G precursor.

[0121] (4) The ALPF@G precursor in step (3) was heated to 1200℃ for 2h under a nitrogen atmosphere and a gas flow rate of 50mL / min to obtain lignin phenolic resin coated graphite anode material, named ALPF@G-1200.

[0122] Comparative Example 3

[0123] (1) Prepare 35 mL of ethanol-water solution with a volume ratio of 1:1. Add 5 g of nano-graphite, 0.5 g of lignin, 0.5 g of phenol and 2.5 mL of ammonia as catalysts to the ethanol-water solution. Stir in an oil bath at 30 °C for 1 h until completely dissolved. Then add 2 mL of formaldehyde solution with a concentration of 1.25 mol / L. Stir in an oil bath at 60 °C for 3 h. Then raise the temperature to 90 °C and stir in an oil bath for 3 h.

[0124] (2) The liquid in step (1) is heated and stirred at 90°C for 8 hours for the first drying to obtain a wet coating material, named ALPF@NG.

[0125] (3) Place the ALPF@NG obtained in step (2) in an 80℃ oven for a second drying for 24h to obtain the dried ALPF@NG precursor.

[0126] (4) The ALPF@NG precursor in step (3) was heated to 1200℃ for 2h under a nitrogen atmosphere and a gas flow rate of 50mL / min to obtain lignin phenolic resin coated nano-graphite anode material, named ALPF@NG-1200.

[0127] Table 1

[0128]

[0129] Table 1 shows that constructing a uniform coating layer on the surface of nano-graphite and hard carbon can passivate defect sites on the particle surface, suppress side reactions between the electrolyte and the graphite matrix, and regulate the orderly and stable formation of the SEI film, ultimately achieving a simultaneous improvement in the initial charge-discharge efficiency and cycle stability of the anode material. The introduction of different coating systems also had a certain impact on the electrochemical performance of the materials. Among all tested samples, ALPF@NG-HC-1200 exhibited the best electrochemical performance.

[0130] In terms of lithium storage performance, the second-stage plateau capacity of ALPF@NG-HC-1200 reaches 310 mAh·g. -1 Compared to unencapsulated ALPF-1200 (230 mAh·g), -1 This represents a 34.8% increase, and is significantly superior to pure graphite G (270 mAh·g). -1 ), NG (300 mAh·g -1 In other embodiments, the graphite-hard carbon composite coating can fully utilize the lithium storage platform advantages of the graphite matrix, and the sample has a reversible specific capacity of up to 450 mAh·g. -1 This is the highest value among all samples, representing a 21.6% improvement over ALPF-1200, and outperforming all other examples and comparative examples.

[0131] In terms of cycle stability and interface performance, ALPF@NG-HC-1200 exhibits a capacity retention of up to 99%, excellent cycle stability, and an initial coulombic efficiency of 82%. These results demonstrate that the synergistic coating of nano-graphite and hard carbon can construct a stable electrode-electrolyte interface, effectively optimizing interface properties while fully leveraging the excellent lithium storage capacity of nano-graphite.

[0132] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a lignin-based carbon-coated nano-graphite composite anode material, characterized in that, Includes the following steps: (1) Mix nano-graphite, hard carbon, lignin, phenolic compounds, ethanol aqueous solution and ammonia water, heat and stir the resulting mixture until completely dissolved, add formaldehyde solution and heat to react, and dry to obtain lignin phenolic resin coated nano-graphite composite material precursor. (2) The precursor is carbonized in an inert gas atmosphere to obtain the coating material.

2. The preparation method according to claim 1, characterized in that, The mass ratio of nanographite to lignin is 20:1 to 2:1, the mass ratio of hard carbon to nanographite is 10:1 to 1:10, and the mass ratio of lignin to phenol is 3:1 to 1:

3.

3. The preparation method according to claim 2, characterized in that, The mass ratio of nanographite to lignin is 10:1 to 5:1, the mass ratio of hard carbon to nanographite is 2:1 to 1:3, and the mass ratio of lignin to phenol is 1 ± 0.5:

1.

4. The preparation method according to claim 1, characterized in that, In step (1), the mass concentration of ethanol in the mixture is 20%-40%, and the mass concentration of ammonia is 1%-10%.

5. The preparation method according to claim 4, characterized in that, The volume ratio of ethanol to water in the ethanol-water solution is 1 ± 0.5:1; the mass concentration of the ammonia solution is 2%-5%.

6. The preparation method according to claim 1, characterized in that, The mass ratio of formaldehyde to lignin is 1 ± 0.5:10; the mass concentration of the formaldehyde solution is 1%-5%.

7. The preparation method according to any one of claims 1 to 6, characterized in that, The heating reaction in step (1) is carried out at a temperature of 50℃ to 100℃ for 1h to 24h; the carbonization in step (2) is carried out at a temperature of 800℃ to 1500℃ for 1h to 4h.

8. The preparation method according to claim 7, characterized in that, The heating reaction in step (1) is carried out at a temperature of 60±5℃ for 3±1h, and then the temperature is raised to 90±5℃ for 3±1h; the carbonization in step (2) is carried out at a temperature of 1000~1200℃ for 2±0.5h. And / or, the heating rate of carbonization in step (2) is 1 to 30 °C / min, and the flow rate of the inert gas is 2 to 100 mL / min; more preferably, the heating rate of carbonization is 5 °C / min, and the flow rate of the inert gas is 50 mL / min. And / or, the lignin in step (1) is at least one of alkali lignin, enzymatically hydrolyzed lignin, and lignin sulfonate; And / or, the phenolic compound in step (1) is at least one of phenol, cresol, and xylenol; and / or, the drying temperature in step (1) is 60-80°C and the time is 12-36h.

9. The lignin-based carbon-coated nano-graphite composite anode material prepared by the method according to any one of claims 1 to 8.

10. The application of the lignin-based carbon-coated nano-graphite composite anode material according to claim 9 in lithium-ion batteries.